Examining the functions of prison critical incidents: a preliminary qualitative analysis of public reporting. Issue 2 (11th June 2018) - Hughes, Cameron; Ireland, Jane L.; Ireland, Carol A.
Abstract : Purpose: The purpose of this paper is to explore the function of crisis incidents in prisons within the UK and USA. The incidents reviewed included riots and hostage incidents, focusing only on information that was available publically. It did not intend to capture official reports not in the public domain. Design/methodology/approach: Publically available information on incidents were systematically reviewed. Functional assessment and grounded theory were employed to examine background factors, triggers and maintaining factors. In total, 25 crisis incidents were analysed (UK =10 and USA =15) from the past 30 years. It was predicted that crisis incidents would be motivated by negative and positive reinforcement, with negative more evidenced than positive. Precipitating factors (i.e. triggers) were predicted to include negative emotions, such as frustration and anger. Findings: Similarities in triggers and background factors were noted between hostage taking and riot incidents. Positive reinforcement was primarily indicated. Riots appeared driven by a need to communicate, to secure power, rights, control and/or freedom, whereas for hostage taking these functions extended to capture the removal of negative emotions, to inflict pain, to punish/gain revenge, to effect a release, to manage boredom and to promote positive emotions. Research limitations/implications: The study is preliminary and focused on the reporting of incidents in publically available sources; consequently, the data are secondary in nature and further limited by sample size. Nevertheless, it highlights evidence for similarities between types of crisis incidents but also some important potential differences. The need to understand the protective factors preventing incidents and minimising harm during incidents is recommended. Practical implications: It highlights evidence for similarities between types of critical incidents but also some important potential differences. Understanding differences between incidents is important in the tailoring of specific policies to address these areas. Understanding motivation and reinforcement is valuable in working towards the prevention of critical incidents. Understanding the protective factors preventing incidents and minimising harm during incidents is recommended. Originality/value: This is an under-researched area. The study contributes to the field not only by focusing on providing a detailed analysis of an under-used source (public reporting) but by also identifying where gaps in research remain. The results demonstrate the value in understanding incidents through their motivation, particularly in distinguishing between negative and positive reinforcement.